2015
DOI: 10.5152/jtgga.2015.15073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anesthesia type on short-term postoperative cognitive function in obstetric patients following cesarean section

Abstract: Conclusion:We concluded that general anesthesia with sevoflurane or desflurane and spinal anesthesia had no effects on cognitive functions in patients undergoing cesarean operation. (J Turk Ger Gynecol Assoc 2015; 16: 219-25) Keywords: Sevoflurane, desflurane, general anesthesia, spinal anesthesia, cognitive function, cesarean section Received: 16 April, 2015 Accepted:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Two studies [28,37] based on data from 121 patients showed that the use of BIS did seem to prevent POD within 1-5 days after surgery. In contrast, findings from two studies [26,34] involving 135 patients showed a neutral effect of the use of BIS monitoring.…”
Section: Bis Vs No Bis: Podmentioning
confidence: 59%
See 3 more Smart Citations
“…Two studies [28,37] based on data from 121 patients showed that the use of BIS did seem to prevent POD within 1-5 days after surgery. In contrast, findings from two studies [26,34] involving 135 patients showed a neutral effect of the use of BIS monitoring.…”
Section: Bis Vs No Bis: Podmentioning
confidence: 59%
“…Twenty-two studies were removed based on abstract screening. Finally, fourteen studies were included in the systematic review [26][27][28][29][30][31][32][33][34][35][36][37][38][39] eight of which [29][30][31][32][33][36][37][38] were qualified to be in the meta-analysis (for reasons, see Fig 1).…”
Section: Study Protocol and Protocol Deviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…And the recovery from general anesthesia is usually assessed by monitoring behavioral and physiological signs [47]. The rapid response of anesthesia may cause cognitive dysfunction in experimental animals, and the delayed recovery or incompletely recovery of brain nerve function may result in postoperative cognitive function obstacle [48, 49]. In this study, the proportion of δ waves in ECoG was used to evaluate the depth of anesthesia, the duration of LORR and period of ataxia were assessed the anesthesia time or recovery of motor function, Morris water maze was used to evaluate the spatial learning and memory.…”
Section: Discussionmentioning
confidence: 99%